Physical and emotional sibling violence among South Asian immigrants in the United States - Perkins, Nathan H. (Journal of family violence, 2024)
Purpose: To date, no research has been conducted examining physical and emotional sibling violence in South Asian immigrants in the U.S. This retrospective, exploratory study examined the associations between physical and emotional sibling violence and age, gender, immigrant generation status, and number of siblings in childhood in a sample of South Asian immigrants in the United States. Methods: This study uses data from a subsample (N = 674) of South Asian immigrants within the United States, who had at least one sibling in childhood, from a larger study examining responses to a bystander intervention pilot study (N = 974). Participants were asked about the frequency in which they experienced behaviors (as both perpetrator and victim) associated with physical and emotional sibling violence with their closest-aged sibling in childhood. Participants were also asked about their age, gender, immigrant generation status, and number of siblings in childhood. Results: Through a series of chi-square analyses, associations were identified between frequency of violent behaviors and gender, immigrant generation status, as well as number of siblings in childhood, but not for each group of participant-to-sibling physical, sibling-to-participant physical, participant-to-sibling emotional, sibling-to-participant emotional. A series of four exploratory ordinal regression models found associations of age, gender, and number of siblings with sibling violence frequency groups, but not for immigrant generation status. Conclusion: These findings highlight the need for future research examining physical and emotional sibling violence with South Asian immigrants, including the context in which it occurs. The results also support the need for more psychoeducation for South Asian families and children on the potential implications of this form of family violence in family systems.